To Feel, or Not to Feel, is it a Question of Time? The Influence of Feedback Availability on the Magnitude of Anticipated Regret - Qijia Chen (The Journal of Undergraduate Research, 2013)
Anticipated regret refers to the main psychological effects of the various worries that beset a decision maker before any losses actually materialize (Janis &Mann, 1977). There has been ample research on how anticipated regret might influence people’s subsequent behaviors (e.g., Zeelenberg, 1999), but little work has examined what might affect the magnitude of anticipated regret. The present study aims to investigate the role of availability of outcome. Specifically, the authors are interested in whether the outcome is immediately available or not, we suspected, might influence how much anticipated regret decision makers experience. The result reveals that people indeed experience greater anticipated regret when the outcome is immediately available. The finding contributes to our understanding of anticipated regret by illustrating possible influences posed by temporal distance of feedback. Furthermore, the finding offers implications for decision-making process.